Empiryczny test jednorodności dla metody Warda stosowanej do analizy zbioru województw Polski - Basiura, Beata (Empirical Homogeneity Test for Ward's Method Applied to the Set of Polish Provinces, 2005)
A one-sided homogeneity test allowing to stop an agglomerative process in Ward's method is presented in the paper. This approach has been proposed by Sokołowski in 1992, but critical values have been given only for n = 49. The results for n = 16 are presented in this paper. Rough critical values are found by analysis of data sets generated by the multidimensional normal distribution. Then they are smoothed using some analytical functions dependent on a number of object and the number of attributes. Functions appeared to fit extremely well. If hypothesis H0 about the homogeneity is not true then at some stage of sub-groups agglomeration process the agglomerative distances are greater then they should be assuming the hypothesis H0 is true.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 171-179